2016
DOI: 10.1186/s40064-016-2950-6
|View full text |Cite|
|
Sign up to set email alerts
|

Japanese traditional dietary fungus koji Aspergillus oryzae functions as a prebiotic for Blautia coccoides through glycosylceramide: Japanese dietary fungus koji is a new prebiotic

Abstract: Background The Japanese traditional cuisine, Washoku, considered to be responsible for increased longevity among the Japanese, comprises various foods fermented with the non-pathogenic fungus Aspergillus oryzae (koji). We have recently revealed that koji contains an abundant amount of glycosylceramide. Intestinal microbes have significant effect on health. However, the effects of koji glycosylceramide on intestinal microbes have not been studied.Materials and methodsGlycosylceramide was extracted and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 61 publications
(68 reference statements)
1
40
0
Order By: Relevance
“…As previously reported, the administration of dietary yeast increases the population of Lactobacillales and decreases the Bacteroides in mice [11]. Another report demonstrated that the intake of yeast changes the gut microbial composition, and the genus Lactobacillus is only detected in yeast-fed groups [12] Also, the intake of glycosylceramide, derived from rice malt, was reported to increase Blautia coccoides in mice [13]. From these results, amazake made of both rice malt and sake cake was expected to improve the intestinal function.…”
Section: Introductionmentioning
confidence: 75%
“…As previously reported, the administration of dietary yeast increases the population of Lactobacillales and decreases the Bacteroides in mice [11]. Another report demonstrated that the intake of yeast changes the gut microbial composition, and the genus Lactobacillus is only detected in yeast-fed groups [12] Also, the intake of glycosylceramide, derived from rice malt, was reported to increase Blautia coccoides in mice [13]. From these results, amazake made of both rice malt and sake cake was expected to improve the intestinal function.…”
Section: Introductionmentioning
confidence: 75%
“…There is a strong relationship between decreased levels of genus Blautia and diseases. Increasing the ratio of Blautia in the intestine might be beneficial for health [29]. An increase of Blautia coccoides through the intake of Japanese koji might be one mechanism explaining Japanese longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshimoto et al (2004) reported that SSDB treated with Bacillus subtilis and cellulase is rich in caffeic acid, one of the many polyphenols that has beneficial physiological functions. In addition, glucosylceramide contained in the koji mold is capable of acting as a prebiotic (Hamajima et al, 2016), and barley-derived β-glucan improves metabolism in mice fed high-fat diet through short chain fatty acids (SCFAs) produced by intestinal bacteria (Miyamoto et al, 2018). It is also observed that Aspergillus species also contain polysaccharides, such as β-glucan (Ishibashi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%